2014
DOI: 10.3810/psm.2014.05.2054
|View full text |Cite
|
Sign up to set email alerts
|

Nonprescription Pain Medication Use in Collegiate Athletes: A Comparison of Samples

Abstract: Athletes from NCAA Division II and Division III sports appear to use nonprescription pain medication for sports-related pain less often and have lower rates of misuse than do Division I-A football athletes. Division I-A football athletes may be more likely to misuse nonprescription pain medication than non-Division I-A athletes. Special attention should be paid to this population to help reduce adverse event risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…11,17,18,26,58,75,80 Other studies surveyed collegiate athletes. 38,46,64,74,82 In addition, some studies provided estimates through analysis of drug chemistry results (in-or out-of-competition). 26-28, 32, 57, 65 8 Oral or non-specific route NSAIDs NSAIDs are the most frequently studied and reported to be the most frequently used pain medication.…”
Section: Studies Of Medication Usementioning
confidence: 99%
See 2 more Smart Citations
“…11,17,18,26,58,75,80 Other studies surveyed collegiate athletes. 38,46,64,74,82 In addition, some studies provided estimates through analysis of drug chemistry results (in-or out-of-competition). 26-28, 32, 57, 65 8 Oral or non-specific route NSAIDs NSAIDs are the most frequently studied and reported to be the most frequently used pain medication.…”
Section: Studies Of Medication Usementioning
confidence: 99%
“…46 Finally, three other studies of collegiate athletes surveyed use of all non-prescription over-the-counter medications combined, including NSAIDs, paracetamol, and others. 64,74,82 These studies found use of over-thecounter analgesic medications by 58% to 73% of athletes. These studies also reported athletes lacked awareness about adverse effects, 74 had significant external influence to use pain medications, and frequently misused pain medications, 74,82 especially collegiate American football players.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Thus, the prevalence of pain may be underreported in the sports medicine literature with only a few studies reporting pain on collegiate athletes or exploring sex difference of pain. 8,9,14 Impact of pain on athlete availability, training and performance can be mitigated when key epidemiological information is used to inform adequate pain management strategies. 15 Various methods are used by athletes to minimise the impact of pain during training and competition.…”
Section: Introductionmentioning
confidence: 99%
“…18,21 Since NSAIDs are easy to access and affordable, athletes of all backgrounds frequently use it without any medical advice and has been seen to be used the highest at the high school or professional level. 14,18 Given the potential poor health literacy among athlete population, prolonged use of NSAIDs, particularly prophylactic misuse is concerning. 6,18,22 For example, athletes were unable to differentiate between competition and training related soreness, and injury related pain, potentially leading to indiscriminate pain management strategies.…”
Section: Introductionmentioning
confidence: 99%